Pengaruh Pelatihan Kesehatan Jiwa Terhadap Stigma Kader Pada Orang Dengan Gangguan Jiwa - Ferika Anggun Saputri; Suci Ratna Estria; Siti Nurjanah (Jurnal Keperawatan Florence Nightingale, 2026)
Mental disorders remain a public health problem influenced by negative stigma against people with mental disorders (PMDs). This stigma results in low social acceptance, delayed help seeking, and limited support for the recovery process of people with mental disorders. Mental health cadres play a strategic role in public health services, but data collection shows that most cadres have never received mental health training. This situation indicates the need for interventions in the form of mental health training to reduce stigma against people with mental disorders. This study aims to describe the effect of mental health training on cadre stigma against people with mental disorders. This study used a pre-experimental design with a one group pretest-posttest with a total sampling technique of 40 respondents. The research instrument used was Community Attitudes Toward Mentally Ill (CAMI). Data analysis was conducted using the Shapiro Wilk test and Paired Sample T-test. The results showed an increase in the average stigma score from 75.54 to 84.03 with a p-0.003. It was concluded that mental health training had a positive and significant effect in reducing negative stigma and improving positive attitudes of community health workers toward people with mental disorders